Identification of Multidrug-resistant Salmonella Plasmid Variants Using Polymerase Chain Reaction (PCR) Based Replicon Typing Technique in Ghana - Owusu-Dabo, Ellis; Acheampong, Godfred; Owusu, Michael; Owusu-Ofori, Alex; Osei, Isaac; Sarpong, Nimako; Park, Se Eun; Marks, Florian (Amref Health Africa)
Introduction: Salmonella infections cause significant morbidity and mortality, especially in resource-limited countries. The situation is worsened by widespread presence of multidrug resistant (MDR) strains, largely encoded on conjugative plasmids, but with little knowledge about how these plasmids are identified especially in low-middle income countries. We present findings of various plasmid variants possibly encoding MDR salmonella from Ghana. Methods: this was a cross-sectional study involving individuals suspected of having salmonella infection presenting at two major hospitals in Ghana. Blood, stool and oropharyngeal specimens (OPS) were taken from consenting individuals between May, 2016 and January, 2018. Identification of salmonella was done using standard microbiological procedures. Total DNA was extracted from MDR salmonella isolates and PCR-based replicon typing (PBRT) performed using 30 replicons representative of the major incompatibility groups among Enterobacteriaceae. Results: of 2,376 samples collected, 101 (4.3%) salmonella were isolated. Multidrug-resistant salmonella was detected in 34 (33.7%) strains; S. Typhi (67.6%), NTS (32.4%). Four different incompatibility (Inc) groups were identified by PBRT. Eleven S. Typhi bacteremic isolates (32.4%), harboured plasmids with Inc group HI1 of target size 534bp. The most predominant replicon (13/34; 38.2%) belonged to IncU plasmid. Non-typhoidal salmonella harboured 1 rare IncX2 plasmid and 8 IncFIIS plasmids known to encode resistance to carbapenems, colistins and several virulence genes. Conclusion: this study shows presence of circulating plasmid variants likely to confer MDR in salmonella from clinical isolates. This is the first time Ghana has reported 3 (IncU, IncFIIS, IncX) of 4 variants and these are similar to those circulating in Africa but one (IncFIIS).
© Ellis Owusu-Dabo et al. Africa Health Agenda International Journal - . This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: Ssalmonella Typhi; Non-typhoidal salmonella; Multidrug resistance; Polymerase chain; Reaction; Replicon typing